2020
DOI: 10.1002/imhj.21901
|View full text |Cite
|
Sign up to set email alerts
|

Mind‐mindedness versus mentalistic interpretations of behavior: Is mind‐mindedness a relational construct?

Abstract: Mind-mindedness is a measure of the tendency to represent significant others in internal state terms and is central to supportive parent-infant relationships. The two studies reported here explored whether mind-mindedness generalizes to representations of unknown individuals, using a novel task that assessed individual differences in adults' tendency to interpret others' behavior with reference to their internal states: the Unknown Mother-Infant Interaction Task (UMIIT). We compared UMIIT performance with meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Importantly, mind-mindedness is a cognitive-behavioral trait ( Meins et al, 2011a ; Kirk et al, 2015 ), characterizing a relational construct that is a quality of close relationships ( Meins et al, 2014 ; Larkin et al, 2021 ) and distinct from general parenting sensitivity and supportiveness (e.g., see Meins et al, 2002 , 2003 , 2012 , 2013 ). It is a particular form of mentalization that characterizes the parent’s psychological orientation to the child’s mental states underlying observable behaviors ( Meins, 1997 ; Meins et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, mind-mindedness is a cognitive-behavioral trait ( Meins et al, 2011a ; Kirk et al, 2015 ), characterizing a relational construct that is a quality of close relationships ( Meins et al, 2014 ; Larkin et al, 2021 ) and distinct from general parenting sensitivity and supportiveness (e.g., see Meins et al, 2002 , 2003 , 2012 , 2013 ). It is a particular form of mentalization that characterizes the parent’s psychological orientation to the child’s mental states underlying observable behaviors ( Meins, 1997 ; Meins et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, for both expectant mothers and fathers, individual differences in prenatal mind‐mindedness were unrelated to parents' education, perceived social standing, indices of poor mental health, anticipated involvement in childcare, or knowledge of infant sex. This evidence of discriminant validity adds further weight to the hypothesis that the tendency to think of one's future infant as a sentient being does not reflect differences in parents' state of mind (Larkin et al., 2021 ). Furthermore, the similarity between expectant mothers and fathers demonstrates that a physical link is not a prerequisite for a psychological connection.…”
Section: Introductionmentioning
confidence: 71%
“…Indeed, the lack of within‐couple concordance in mind‐mindedness provides further support for the relationship‐specific nature of mind‐mindedness (Meins et al., 2014 ). Future research examining associations between mind‐mindedness, other parental mentalizing dimensions (e.g., parental reflective functioning; Fonagy et al., 1991 ) and general mentalizing abilities (e.g., Unknown Mother‐Infant Interaction Task; Larkin et al., 2021 ) and prospective links with parent‐child interaction quality, will help tease apart the relative overlap between specific representational dimensions and their unique contribution to later parent and child outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that impaired mentalizing does not reflect an isolated mentalizing deficit but should be understood in terms of different combinations of imbalances across dimensions (Fonagy & Luyten, 2009). In addition, rather than being solely a trait‐like capacity, mentalizing is a dynamic function that is influenced by personal and/or situational factors (Fonagy et al., 1998; Larkin et al., 2021; Luyten et al., 2017b). Thus, having the capacity to reflect upon mental states in one context is not necessarily indicative of being able to make use of such capacity in other contexts (Fonagy et al., 1998).…”
Section: Introductionmentioning
confidence: 99%